Pathology of fatal lineage 1 and 2 West Nile virus infections in horses in South Africa - June H. Williams (Journal of the South African Veterinary Association, 2014)
Since 2007, West Nile virus (WNV) has been reported in South African horses, causing severe neurological signs. All cases were of lineage 2, except for one case that clustered with lineage 1 viruses. In the present study, gross and microscopic lesions of six South African lineage 2-infected horses and the one lineage 1 case are described. Diagnoses were confirmed by real-time reverse-transcriptase polymerase chain reaction (RT-PCR) of central nervous system (CNS) tissue and one by RT-PCR of a brain virus isolate. The CNS of all cases was negative by RT-PCR or immunohistochemistry (IHC) for African horse sickness (AHS), equine encephalosis virus, equine herpes viruses 1 and 4, other zoonotic flaviviruses, alphaviruses, and shunivirus, and either by immunofluorescence or IHC for rabies. Gross visceral lesions were nonspecific but often mimicked those of AHS. The CNS histopathology of WNV lineage 2 cases resembled the nonsuppurative polioencephalomyelitis reported in the Northern Hemisphere lineage 1 and recent Hungarian lineage 2 cases. Occasional meningitis, focal spinal ventral horn poliomalacia, dorsal and lateral horn poliomyelitis, leucomyelitis, asymmetrical ventral motor spinal neuritis and frequent olfactory region involvement were also seen. Lineage 2 cases displayed marked variations in CNS lesion severity, type and distribution, and suggested various viral entry routes into the CNS, based on findings in experimental mice and hamsters. Lineage 1 lesions were comparable to the milder lineage 2 cases. West Nile virus IHC on CNS sections with marked lesions from all cases elicited only two antigen-positive cells in the olfactory cortex of one case. The presence in the CNS of T-lymphocytes, B-lymphocytes, plasma cells and macrophage-monocytes was confirmed by cluster of differentiation (CD) 3, CD20, multiple myeloma oncogene 1 (MUM1) and macrophage (MAC) 387 IHC.